COVID-19 Clusters at Workplaces and its Transmission into Communities in Vietnam: A Novel Emerging Occupational Risk Factor at Work Due to Coronavirus Infection - Huynh, Nhi Ngoc Yen; Nguyen, Dai Duc; Ta, Nguyen Ha; Nguyen, Minh Thien; Nguyen, Tai Van; Dang, Huy Thanh; Vo, Tuyen Kim Cat; Le, Ngoan Tran (Asian Pacific Journal of Environment and Cancer, 2020)
Aims: This study aimed to describe the characteristics of the workplace-related clusters of COVID-19 and its transmissions into communities in Vietnam. Methods and Material: We accessed the database of COVID-19 by the Ministry of Health, Vietnam. Variables included sources of infection, age, sex, nationality, the dates of onset of symptoms and discharge from hospitals, and ID of each patient tested positive with COVID-19. Information from each patient was linked to the sources of infection to identify workplace-related clusters. Among 314 patients, we excluded 43 cases related to two charter flights, the remaining 271 cases were eligible for the study. Results: The biggest cluster of hospital canteen included 26 workers and their 31 family members or hospital’s patients. The second biggest cluster included a pilot of the Vietnam airlines and other 16 patients who have close contact with him at the Bar Buddha at Ho Chi Minh City. A total of 87 patients (32.1% of 271 cases) were related to these workplace-related clusters. The suspected time and the clinical course was significantly longer in the workplace-related clusters than other patients (mean 6.52 vs. 4.05 days, p=0.0191) and (mean 28.71 vs. 20.52 days, p=0.0005), respectively. Conclusions: Because COVID-19 infection at workplaces was responsible for nearly one-third of the total patients, there was a novel emerged occupational risk factor at work due to coronavirus infection. Safety at the workplace in preventing COVID-19 transmission is highly needed.